2013
DOI: 10.1111/jpc.12485
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Milestones’: A randomised controlled trial evaluating an innovative digital resource teaching quality observation of normal child development

Abstract: Aims The study aimed to create and evaluate the educational effectiveness of a digital resource instructing paediatric trainees in a systematic approach to critical and quality observation of normal child development. Methods A digital educational resource was developed utilising the skills of an expert developmental paediatrician who was videoed assessing normal early child development at a series of critical stages. Videos illustrated aspects of language, sophistication of play and socialisation, cognition, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…Four studies [44,47,58,66] compared ODE with self-directed learning, of which only two studies [58,66] reported numerical data. Le et al [66] reported a change in mean attitude scores (SMD 0.46, 95% CI –0.38 to 1.30 [low certainty]) and Sullivan et al [58] assessed attitude posttest (SMD –0.01, 95% CI –0.28 to 0.26 [low certainty]).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four studies [44,47,58,66] compared ODE with self-directed learning, of which only two studies [58,66] reported numerical data. Le et al [66] reported a change in mean attitude scores (SMD 0.46, 95% CI –0.38 to 1.30 [low certainty]) and Sullivan et al [58] assessed attitude posttest (SMD –0.01, 95% CI –0.28 to 0.26 [low certainty]).…”
Section: Resultsmentioning
confidence: 99%
“…Le et al [66] reported that ODE may be as effective as self-directed learning for improving physicians’ attitude. Connolly et al [44] and Sullivan et al [58] reported mixed results. Overall, empirical evidence from the four studies reported mixed results for this outcome.…”
Section: Resultsmentioning
confidence: 99%
“…The conceptual framework most widely used in medical education research is the Kirkpatrick classification that categorizes the outcome to either perception or knowledge of the trainee to change in patient outcomes (42). This framework suggests educational research that ultimately improves patient care has the biggest effect (Table 5) (50).…”
Section: Rigor In Education Researchmentioning
confidence: 99%
“… Self‐rated measures of confidence regarding clinical approach to the child with a first unprovoked seizure and satisfaction with instruction were administered pre‐ and post‐teaching based upon scales previously used in other studies . A series of statements was presented with responses entered on a 5‐point Likert‐type scale ranging from 1 ( strongly disagree ) to 5 ( strongly agree ).…”
Section: Methodsmentioning
confidence: 99%